Arabic Language Acquisition in Boarding High School Students: A Study of Environment, Motivation, and Social Interaction - Asrofi, Imam; Supriatna, Amir; R, Ari Abdul Kohar; Ruswandi, Agus (Lughawiyah: Journal of Arabic Education and Linguistics, 2025)
Arabic language acquisition in boarding schools exhibits distinctive dynamics shaped by immersive environments, institutional policies, and social interaction. Previous studies have primarily examined these factors separately, resulting in a limited integrative understanding. This study explores patterns of Arabic acquisition through the interrelationship between environmental design, motivational mechanisms, and social interaction in three Islamic boarding senior high schools in West Java. Using a qualitative phenomenological approach, participants were purposively selected from schools implementing Arabic programs. Data were collected through in-depth interviews, participatory observation, and document analysis, and analysed using Moustakas’ thematic procedures. The findings reveal three acquisition models. SMA Asy-Syifa represents a classical, fragmented model emphasising grammatical mastery with minimal communicative exposure. FIBBIS High School applies an immersion–regulatory model through language zones and sanctions, increasing exposure but also generating anxiety and silence strategies. In contrast, Yaspida High School implements an integrative ecosystem model that combines a structured language environment, positive incentives, and layered peer support, effectively reducing affective barriers and fostering authentic communicative competence.